Influencia del tiempo de calcinación en hidroxiapatita producida a partir de cáscara de huevo sobre el tamaño de grano y el grado de cristalinida - Estrada Ninatanta, Diego Alejandro (2023)
The present research work developed synthetic hydroxyapatite from chicken eggshell (Gallus gallus) evaluating the influence of calcination time from 1 hour to 4 hours under a constant temperature of 1000°C on behavior of grain size and index of crystallinity. For this, the following procedure was followed: Cleaning of the egg shell and separation of the membrane, drying, pulverizing, sieving, calcining at 800°C for 6 hours, phosphating and calcining at 1000°C. The samples were characterized through X-ray diffraction using the Rigaku brand diffractometer, Miniflex 600 model. The results showed that the highest crystallinity index is obtained under a calcination time of 2 hours with a value of 58.85% and a size of 61,510 nm grain; however, the smallest grain size corresponds to a calcination time of 3 hours with a value of 57.740 nm and a crystallinity index of 57.33%. This shows that the calcination time of hydroxyapatite influences the grain size and the degree of crystallinity of this. This shows that the calcination time of hydroxyapatite influences its grain size and its degree of crystallinity; obtaining recommended values which will serve as a basis for studies and development of biomaterials oriented to the reuse of resources.